Phase transitions in two complex systems confined planar growth for biological systems and multi-lane traffic flow - Domingo, Felicisimo S. (2000)
The presence of phase transitions in two non-physical complex systems: 1) confined planar growth in biology and 2) bi-directional multi-lane traffic flow in investigated using the Monte Carlo simulation technique. In the first system, chains formed by self-avoiding hard spheres undergo confined planar growth. Complex structures arise from the stochastic interplay of two simple opposing mechanisms: enforced connectivity and self-avoidance between spheres. Depending on the value of the parameter T, which sets the tendency of growth along a definite direction, the resulting structures settle into their box-limited or a self-trapped configuration. The presence of a critical point for the phase transition between these two configurations is ascertained. For the second system, a bi-directional stochastic cellular automation (CA) model is presented. The resulting flow patterns arise form the interplay of two opposing tendencies: the tendency to accelerate to minimize travel time and to decelerate to avoid the slower cars ahead. Unlike the first system, there is another instance of opposing tendencies present: switching to other lane to avoid slower vehicles and switching back to the proper lane to avoid incoming traffic. It was observed that the time to deadlock could vary either linearly or non-linearly with respect to road length, depending on the value of the parameter e, which indicates the frequency of vehicular entrance. The presence of a phase transition in this system, as indicated by the change of behavior about e, is alos ascertained.
Research project funded by the University through the Office of the Vice-Chancellor for Research and development (OVCRD).
"March 2000."
Thesis (M.S. Physics)--University of the Philippines Diliman.
Keywords: Phase transformations (Statistical physics); Critical phenomena (Physics); Biological systems; Traffic flow